Etuaptmumk/Two-Eyed Seeing as a Framework for Sustainable and Inclusive Tourism Planning and Development - Anderson, Eleanor (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2025)
Indigenous voices and philosophies are conspicuously absent from the call to transform tourism planning through regenerative and culturally inclusive approaches. To address this, this work explores collaborative frameworks that can propel the tourism industry forward for all stakeholders in a more inclusive and sustainable way. Examining the role of Traditional Knowledge in Unama’ki Cape Breton Island provides an enhanced understanding of the barriers to and opportunities for Indigenous inclusion in tourism decision-making and can inform a broader world view. Additionally, the philosophy of Etuaptmumk/Two-Eyed Seeing allows for the consideration of two distinct perspectives and could be usefully applied to the tourism industry. Through the lens of reconciliation, Etuaptmumk/Two-Eyed Seeing provides a path for tourism decision-makers to contribute to a shared decision matrix and, ultimately, to contribute to a new framework for tourism development. Challenging established colonial research norms and exploring the complex dynamic between Indigenous and non-Indigenous decision-making will deliver both a theoretical contribution to existing literature as well as a practical contribution to building tourism on more equitable grounds.